Hall currents and EDL effects on multiphase wavy flow of Carreau fluid in a microchannel having oscillating walls: A numerical study - Alqarni, M. M.; Riaz, Arshad; Firdous, Muazma; Lali, Ikram Ullah; El-Din, ElSayed M. Tag; Rahman, Shafiq ur (Frontiers in Physics, 2022)
In current analysis, the authors have disclosed the effects of electro-osmosis on the multiphase flow of Carreau fluid in a microchannel in the presence of Hall currents and solid particles. Moreover, the channel walls have been considered as compliant which are subject to oscillation occurring at the surface. To investigate the problem quantitatively, mathematical models for fluid phase and particulate phase have been structured. A lubrication approach has been appealed due to laminar flow and small channel dimensions. In order to achieve a resulting data, system of differential equations has been handled by the help of a numerical process performed on Mathematica through a built-in NDSolve tool. The results are finally discussed graphically to examine the effects of various physical factors on the flow quantities. From pictorial discussion, it is gathered that Helmholtz-Smoluchowski velocity parameter and presence of increasing amount of solid particles affects the heat exchange in increasing manner while electro-kinetic energy. It is also convincing that velocity is a direct function of solid particles, compliant walls but inverse link is noticed against the electro-kinetic energy presence. Such studies can be employed in microfluidic devices and are also productive in medical and mechanical research.